Efektif Komunikasi pada Pasangan Menikah dengan Disfungsi Sexual - zakiah, zakiah (JURNAL KEBIDANAN BESTARI, 2022)
Background: Sexual dysfunction is the cognitive, affective and / or behavior deprive someone or couples to be involved and / or enjoy sexual intercourse and satisfying achieve orgasm.This is caused by biologic, psycologic and interpersonal factors. Biological causes may be a physical disturbance, disease, and the effects of medicines.Use medicine as a therapy is not always can resolve sexual dysfunction in women, needed multi handling sector. Method:This research was a descriptive research with a case study in November 2022. Cases report: a woman 40 years old, married 20 years, complain pain on her genital area after sexual intercourse since 3 days ago, she was an acceptors of pills combination since 2,5 years, sexual frequency 5-6 times a week. IVA test result was negative. The treatmet: deep breath techniques to reduce pain, effective communication approach about health and safe sexual intercourse, use of a lubricant, keep the genital area clean to avoid infection and maintain a healthy lifestiye. Conclusion: Effective communication plays an important role in overcoming couples with sexual dysfunction, with effective communication it is hoped that partners will achieve sexual satisfaction. Key words: Sexual dysfunction, effective communication